Histological examination of porcine oviduct, ovary, cumulus-oocyte complexes, and follicular fluid secretion - Panyarachun, Busaba; Chuen-Im, Thanaporn; Khongkarat, Phanthiwa; Gumlungpat, Nongnuch; Panyarachun, Panadda; Youngsabanant, Mayuva (Science, Engineering and Health Studies, 2021)
The porcine reproductive system, while inedible, is a valuable source of hormone and growth factors for cell maturation. The present study investigated the morphological features of the oviduct, ovary, and cumulus-oocyte complexes of Large White pigs and protein patterns of the follicular fluid in the ovaries. Pig ovaries (n=71) were collected from local slaughterhouses in Nakhon Pathom Province, Thailand. A total of 3,510 oocytes were obtained and categorized based on follicle size as small (1-3 mm in diameter; n=2,910), medium (4-6 mm in diameter; n=530), and large (7-8 mm in diameter; n=70). The examination of oocytes revealed that they were intact cumulus cell layer oocytes, multi cumulus cell layer oocytes, partial cumulus cell layer oocytes, completely denuded oocytes, and degenerated oocytes. The oviduct comprised three anatomical regions: the isthmus, ampulla, and infundibulum. The infundibulum had the largest diameter, whereas the isthmus had the smallest diameter. The protein patterns of the follicular fluid were analyzed via a molecular weight-based approach using sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The results showed that the fluid in both small and medium follicles contained proteins of molecular weights of 23, 50, 100, 225, and >225 kDa. For large follicles, proteins of molecular weights of 12, 16, 23, 50, 100, 225, and >225 kDa were detected in the follicular fluid. These findings would be useful for biotechnological studies in the future.